The effect of theobromine on the in vitro de- and remineralization of enamel carious lesions. Issue 3 (May 2020) - Thorn, Anna K.; Lin, Wei-Shao; Levon, John A.; Morton, Dean; Eckert, George J.; Lippert, Frank
Highlights: The effect of theobromine on de- and remineralization of enamel carious lesions was investigated. Theobromine did not affect lesion de- and remineralization under the chosen conditions. Fluoride and pH affected lesion de- and remineralization. There was no interaction between theobromine and fluoride or theobromine and pH. Abstract: Objectives: This in vitro study investigated the effect of theobromine on the de- and remineralization of enamel carious lesions under plaque fluid-like conditions. Methods: Early carious lesions were created in 272 bovine enamel specimens and assigned to sixteen groups (n = 17) based on Knoop surface microhardness (SMH). Lesions were demineralized again under plaque fluid-like conditions in the presence of fluoride (0.2 or 1 ppm) and theobromine (0; 10; 100 or 200 ppm) at different pH values (5.5 or 7.0) in a factorial design. SMH was determined again and percent SMH recovery (%SMHr) calculated. Three-way ANOVA was used for the fixed effects of fluoride, theobromine and pH levels to compare the differences between each level. Results: The three-way interaction was not significant (p = 0.712). The two-way interaction between fluoride and pH was significant (p = 0.030), whereas those between fluoride and theobromine as well as that for pH and theobromine were not (p = 0.478 and p = 0.998, respectively). Theobromine did not affect %SMHr at any of the tested concentrations. There were trends for the higher fluoride concentration and the higher pH resulting in more rehardening with the lesions exposed to 0.2 ppm fluoride at pH 5.5 displaying significantly less rehardening than those exposed to 0.2 ppm fluoride at pH of 7.0 and lesions exposed to 1 ppm fluoride at pH of 5.5. Conclusion: Theobromine, when continuously present in a plaque fluid-like medium at various concentrations and at different pH values, does not affect de- or remineralization of enamel carious lesions under the presently studied conditions. Clinical significance: Based on the presently available evidence, theobromine cannot be recommended as an anticaries agent.